A proof-of-concept of cross-luminescent metascintillators: testing results on a BGO:BaF2 metapixel. (11th January 2023) - Konstantinou, G; Latella, R; Moliner, L; Zhang, L; Benlloch, J M; Gonzalez, A J; Lecoq, P
Abstract: Objective : Time-of-flight positron emission tomography (PET) is the next frontier in improving the effective sensitivity. To achieve superior timing for time-of-flight PET, combined with high detection efficiency and cost-effectiveness, we have studied the applicability of BaF2 in metascintillators driven by the timing of cross-luminescence photon production. Approach : Based on previous simulation studies of energy sharing and analytic multi-exponential scintillation pulse, as well as sensitivity characteristics, we have experimentally tested a pixel of 3 × 3 × 15 mm3 based on 300 μ m BGO and 300 μ m BaF2 layers. To harness the deep ultraviolet cross-luminescent light component, which carries improved timing, we use the FBK VUV SiPM. Metascintillator energy sharing is addressed through a double integration approach. Main results : We reach an energy resolution of 22%, comparable to an 18% resolution of simple BGO pixels using the same readout, through the optimized use of the integrals of the metascintillator pulse in energy sharing calculation. We measure the energy sharing extent of each pulse with a resolution of 25% and demonstrate that experimental and simulation results agree well. Based on the energy sharing, a timewalk correction is applied, exhibiting significant improvements for both the coincidence time resolution (CTR) and the shape of the timing histogram. We reach 242 ps CTR for the entire photopeak, while for a subset of 13% of the most shared events, the CTR value improves to 108 ps, comparable to the 3 × 3 × 5 mm3 LYSO:Ce:Ca reference crystal. Significance : While we are considering different ways to improve further these results, this proof-of-concept demonstrates the applicability of cross-luminescence for metascintillator designs through the application of VUV compatible SiPM coupling, and easily implementable digital algorithms. This is the first test of BaF2 -based metascintillators of sufficient stoppng power to be included in a PET scanner, demonstrating the industrial applicability of such cross-luminescent metascintillators.